Proceedings of the 2017 Conference on Designing Interactive Systems 2017
DOI: 10.1145/3064663.3064715
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Design Opportunities for a Context-Adaptive Medical Checklist Through Technology Probe Approach

Abstract: This paper explores the workflow and use of an interactive medical checklist for trauma resuscitation—an emerging technology developed for trauma team leaders to support decision making and task coordination among team members. We used a technology probe approach and ethnographic methods, including video review, interviews, and content analysis of checklist logs, to examine how team leaders use the checklist probe during live resuscitations. We found that team leaders of various experience levels use the techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Medical researchers at our study site have previously compared team performance during pediatric trauma resuscitations with and without paper-based checklists [15], observing improvement in the completion of some tasks, as well as increased odds of task completion in the post-checklist implementation period. In a later study, [21] we suggested that the digital checklist for trauma resuscitation could be an effective replacement for the paper form after deploying and evaluating the digital aid through a technology probe approach. Here, we build on this prior work by comparing the effects of two checklist formats on timecritical team performance.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Medical researchers at our study site have previously compared team performance during pediatric trauma resuscitations with and without paper-based checklists [15], observing improvement in the completion of some tasks, as well as increased odds of task completion in the post-checklist implementation period. In a later study, [21] we suggested that the digital checklist for trauma resuscitation could be an effective replacement for the paper form after deploying and evaluating the digital aid through a technology probe approach. Here, we build on this prior work by comparing the effects of two checklist formats on timecritical team performance.…”
Section: Related Workmentioning
confidence: 99%
“…Checklists and other cognitive aids have also caught up with this digitization trend in healthcare [1,7,21,29,33,35]. Checklists are different from EHRs because they support compliance with standardized protocols rather than just documentation.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations